2021
DOI: 10.3390/ijms22179246
|View full text |Cite
|
Sign up to set email alerts
|

Overdominance at the Gene Expression Level Plays a Critical Role in the Hybrid Root Growth of Brassica napus

Abstract: Despite heterosis contributing to genetic improvements in crops, root growth heterosis in rapeseed plants is poorly understood at the molecular level. The current study was performed to discover key differentially expressed genes (DEGs) related to heterosis in two hybrids with contrasting root growth performance (FO; high hybrid and FV; low hybrid) based on analysis of the root heterosis effect. Based on comparative transcriptomic analysis, we believe that the overdominance at the gene expression level plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 138 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…The application of transcriptome analysis in heterosis research has effectively revealed the molecular basis of heterosis in Arabidopsis ( Groszmann et al., 2015 ; Liu et al., 2021 ), rice ( Katara et al., 2020 ), corn ( Song et al., 2013 ; Guttikonda et al., 2020 ), cotton ( Shahzad et al., 2020 ), and soybean ( Zhang et al., 2017 ), but the molecular basis of heterosis in tobacco root growth has not been reported in the literature. In the early stage of tobacco growth, improved root development plays an important role in enhancing the absorption of nutrients and water by plants, promoting their growth and increasing their yield ( Zhang et al., 2020 ; Shalby et al., 2021 ). From this point of view, through comparative transcriptome analysis of roots, the genetic basis of root development heterosis of two strong heterosis hybrids and their parents was studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of transcriptome analysis in heterosis research has effectively revealed the molecular basis of heterosis in Arabidopsis ( Groszmann et al., 2015 ; Liu et al., 2021 ), rice ( Katara et al., 2020 ), corn ( Song et al., 2013 ; Guttikonda et al., 2020 ), cotton ( Shahzad et al., 2020 ), and soybean ( Zhang et al., 2017 ), but the molecular basis of heterosis in tobacco root growth has not been reported in the literature. In the early stage of tobacco growth, improved root development plays an important role in enhancing the absorption of nutrients and water by plants, promoting their growth and increasing their yield ( Zhang et al., 2020 ; Shalby et al., 2021 ). From this point of view, through comparative transcriptome analysis of roots, the genetic basis of root development heterosis of two strong heterosis hybrids and their parents was studied.…”
Section: Discussionmentioning
confidence: 99%
“…In most previous studies, heterosis is usually demonstrated in terms of biomass, yield, and stress resistance ( Fujimoto et al., 2018 ; Li et al., 2021 ). In recent years, however, some studies have shown that the level of heterosis in root traits may be higher than that in the overground part ( Ju et al., 2018 ; Dafna et al., 2021 ), and some efforts have been made to reveal the molecular mechanism of heterosis in root development ( Paschold et al., 2010 ; Shalby et al., 2021 ), which means that the root system may be the perfect organ to study the genetic basis of tobacco heterosis. Although there are several genetic models used to describe heterosis, including dominant, overdominant, and epistasis, but its molecular basis remains poorly understood ( Chen, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAC (NAM, ATAF, and CUC) transcription factors (TFs), as one of the largest family of transcription factors in plants, comprise a complex plant-specific superfamily and presents in a wide range of species [ 4 , 6 ]. NAC TFs were found to function in various growth and development processes, including leaf or flower senescence [ 7 , 8 , 9 ], formation of cell wall [ 10 , 11 ], fruit ripening [ 12 , 13 , 14 ], root growth [ 15 ], etc. Besides, a large number of studies demonstrated that NAC TFs played important roles in abiotic and biotic stress responses, especially in crops.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high‐throughput nucleotide sequencing technology, transcriptome analysis has become an effective tool for studying crop heterosis and has been widely used to explore the molecular processes of hybrid vigor at the transcript regulation aspect in Arabidopsis thaliana , rice, maize, and other crops (Fu et al, 2022; Liu et al, 2020; Ma et al, 2018; Shalby et al, 2021; Sinha et al, 2020; Zhao et al, 2019). Recently, Shalby et al (2021) found that the overdominance at the gene expression level plays a critical role in hybrid roots early biomass heterosis of Brassica napus . Ma et al (2018) identified four important genes that were related to maize heterosis and high planting density by transcriptome analyses.…”
Section: Introductionmentioning
confidence: 99%